Longitudinal study on ultrasound assessment of peripheral arterial elasticity and liver stiffness for evaluating clinical intervention efficacy in children with obesity - Zheng, Ning; Jiang, Qiaosheng; Zou, Lizhen; Fang, Xiaodan; Zhang, Yunjiao (Frontiers in Pediatrics, 2025)
ObjectiveTo evaluate the efficacy of a multidisciplinary clinical intervention in children with obesity by longitudinally monitoring changes in vascular elasticity and liver stiffness via ultrasound-derived parameters.MethodsA single-center longitudinal study was conducted on 120 children with obesity (aged 7–14 years, BMI ≥95th percentile). The participants underwent a 12-month intervention involving personalized low-calorie diets, structured aerobic exercise, and family-based cognitive–behavioral therapy. Vascular parameters (carotid intima–media thickness [IMT], flow-mediated dilation [FMD], elasticity coefficient [Ep], stiffness index [β], distensibility coefficient [CD], arterial compliance [AC]) and liver stiffness [shear wave velocity (SWV)] were assessed at baseline (T0), 6 months (T1), and 12 months (T2) via Siemens S2000 ultrasound with ARFI technology. Statistical analyses included repeated-measures ANOVA, Pearson correlation, and multivariate linear regression.ResultsSignificant improvements were observed in FMD (7.1%–9.5%, P < 0.001), Ep (60.5 kPa–42.3 kPa, P < 0.001), β (6.25–4.55, P < 0.001), CD (10.05 kPa–14.9 kPa, P < 0.001), AC (0.96–1.29 mm2/kPa, P < 0.001), and SWV (1.36 m/s–0.98 m/s, P < 0.001). The carotid IMT did not significantly change (Δ = −0.01 mm, P = 0.16). Multivariate regression identified ΔBMI as an independent predictor of ΔFMD (β = 0.32, P = 0.003) and ΔSWV (β = −0.41, P < 0.001).ConclusionUltrasound-based multiparameter assessment effectively quantifies improvements in vascular and hepatic function following clinical intervention in children with obesity.